2020
DOI: 10.24193/subbnegotia.2020.4.01
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Teams Through the Lenses of Team Leaders: Characteristics, Challenges and Achievements

Abstract: "Teamwork as well as the interest in innovation in business are two of the few constant features of contemporary companies, which manifest themselves within a general context characterized by volatility, uncertainty, complexity, and ambiguity. In a company, the benefits of teamwork are widely acknowledged, whereas innovation in business is a strategic direction. This work is based on empirical research, and its main purpose is to identify the characteristics of the innovative teams, the challenges that they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A study performed in India in the ICT and finance sector analyzed the relationship between diversity and the well-being of employees. Results indicated that instrumental connections mediated the relationship between diversity and well-being, and expressive connections were found to not be associated with this relation; thus, developed policies must consider obtaining well-being as diversity is maintained in companies [63]. Performance is goal for companies from Cyprus, but a study was made to observe this relationship due to workplace diversity in recent years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study performed in India in the ICT and finance sector analyzed the relationship between diversity and the well-being of employees. Results indicated that instrumental connections mediated the relationship between diversity and well-being, and expressive connections were found to not be associated with this relation; thus, developed policies must consider obtaining well-being as diversity is maintained in companies [63]. Performance is goal for companies from Cyprus, but a study was made to observe this relationship due to workplace diversity in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…While in the past diversity could also have the disadvantage of reducing the work teams' efficiency due to the differences in the way individuals interact, employee hostility, or communication difficulties [51], now, in a world where the population of racial minorities is growing, women have different employment roles, diversity influences learning, intergroup behaviors, and social relationships, based on "us" not "they", changing the optics and eliminating the idea of local employees, instead labeling them "global talents" [52][53][54][55], civic and organizational involvement [56], as well as workplace relations [57], innovation, financial performance [58], employment based on ethical principles [59], the existence of several talented candidates, a better customer relationship, the adoption of better decisions [60], the improvement of employees' physical and mental health [61], the improvement of productivity, support for disability issues, the improvement of workplace attractiveness [62], the increase of employee welfare [63], the improvement of perceptions through the efficient communication and settlement of diversity issues, and the reduction of adverse effects by reducing the resistance of those employees who feel threatened by diversity [64,65] based on a solid corporate culture and social responsibility principles. According to the authors' arguments, as employees and managers are open to communicating, having intergroup activities, and relating socially and economically, they will more easily accept a workplace based on diversity, and the company will achieve its development.…”
Section: Hypothesis 3 (H3) Workplace Diversity Is Positively Related ...mentioning
confidence: 99%
“…According to a report by Baijal et al (2022), there are more than 75 million Generation Z in Indonesia, and their purchasing power is expected to reach $132 billion by 2025. Gen-Z, the demographic cohort succeeding millennials, is poised to play a significant role in the global economy, as they enter the workforce and assume greater financial responsibilities (Racolța-Paina & Irini, 2021). Understanding and optimizing their spending habits are crucial for both their financial well-being and the overall health of the world economy.…”
Section: Introductionmentioning
confidence: 99%
“…Z generation dominates the digital workforce and has some strengths and weaknesses in selecting a career. A study conducted by Paina & Irini (Racolţa-Paina & Irini, 2021) showed that they tend to choose a job at the virtual level and prefer the one that does not require work routine and long-term commitment. The skills of gen Z to perform virtual communication, operate various tools, edit video, create content, and other kinds of new jobs in era 4.0 benefit them to adapt to job demand (Agarwal & Vaghela, 2018;Umar, 2020).…”
Section: Introductionmentioning
confidence: 99%